2013
DOI: 10.1007/s00167-013-2725-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of anterior cruciate ligament injuries in sports—Part I: Systematic review of risk factors in male athletes

Abstract: Anterior cruciate ligament injury in male athletes likely has a multi-factorial aetiology. There is a lack of evidence regarding neuromuscular and biomechanical risk factors for ACL injury in male athletes. Future research in male populations is warranted to provide adequate prevention strategies aimed to decrease the risk of this serious injury in these populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 83 publications
0
71
0
2
Order By: Relevance
“…18,[49][50][51] The higher injury rate may be related to the increased medial knee displacement observed among injured athletes with a history of previous injury (Table 1) but also a host of other factors 1,56 . 1,57 In contrast to Hewett et al, 23 we did not detect side-to-side differences in any of the 5 candidate variables among the group of injured players. However, players with a history of previous injury clearly represent a high-risk group.…”
Section: Discussionmentioning
confidence: 99%
“…18,[49][50][51] The higher injury rate may be related to the increased medial knee displacement observed among injured athletes with a history of previous injury (Table 1) but also a host of other factors 1,56 . 1,57 In contrast to Hewett et al, 23 we did not detect side-to-side differences in any of the 5 candidate variables among the group of injured players. However, players with a history of previous injury clearly represent a high-risk group.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis study underlined the multi-factorial nature of noncontact ACL injuries and urgent need to identify new risk factors to improve prevention (7).…”
Section: Discussionmentioning
confidence: 99%
“…Anterior cruciate ligament injury in athletes has a multi-factorial etiology. Some of risk factors for ACL rupture are preventable by some change in environment and training athlete, for example during landing or pivoting (4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…27 Several studies showed a high risk of ACL tears in dry compared to wet conditions, in hot compared to cold season, or in pre-season. 28,29 Orchard in 2005 issued the results of a prospective study on Australian footballers and showed that grass type, additionally to ground hardness or weather conditions, would be accountable for a higher risk of noncontact ACL tears. 30 An epidemiologic study conducted by Dragoo et al in 2012 analyzing football players, found that the percent of ACL tears on artificial grass compared to natural grass was present in games, scrimmages, and practices, and across all divisions.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Most studies on preventive programs aimed to change risk factors for ACL tears rather than decrease injury incidence. 28,29 Even if male professional and recreational athletes comprise the biggest population of total ACL tears, the science behind prevention injury programs is based mainly on research conducted on female athletes, therefore researchers are not ready to offer optimal preventive plans for male sports players. 35 Prevention agendas center their attention on some key features of training: balance, proprioception, plyometrics, strengthening, endurance, and stability.…”
Section: Prevention Programsmentioning
confidence: 99%